SWOT Analysis of Marketing Mix Implementation at Barbershop (Cool Cuts Everyday) Yogyakarta - Nanda Bimantara; Fitroh Adhilla; Purwoko (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Barbershop Cool Cuts Everyday provides a different concept from most barbershops, taking the concept from the music, fashion and skateboard communities with a target market among young people. Not only providing haircut services but also providing hair health consultation services. The main problem of Cool Cuts Everyday customers still come from certain communities, the target customers of Cool Cuts Everyday are at least 10-20 people per day. SWOT analysis is a methodical way to identify various aspects to determine a company's approach. An approach to strategic planning that evaluates the prospects, threats, vulnerabilities, and strengths of a company's projects or specializations. The total strengths and weaknesses of the company's internal environment and its external opportunities and threats are among the elements that go into a SWOT analysis. This study uses a case study methodology. Cool Cuts Everydaymust maintain the quality of products/services (haircut results, hair care and styling), cleanliness, comfort and closeness to customers and continue to develop skills and knowledge about the world of barbershop, both in the cutting process, tools used and haircut models. Opening branches or moving locations closer to the main road. Some of the causes of this are that the promotion carried out by Cool Cuts Everyday is not optimal, both online and offline, customers only know about Cool Cuts Everyday based on recommendations from friends to friends, the place/location of Cool Cuts Everyday is difficult to find or visit because it is in a coffee shop area (UD Mitra), besides that the area of ??Cool Cuts Everyday is only 10x5 meters.